Sistem Sharing Profit Pada Marketing Perspektif Hukum Ekonomi Syari’ah (Studi pada CV Bonzela Property Apartement Grand Kamala Lagoon, Bekasi) - Pratama, Adi; Kartika, Kartika; Muflihah, Lilih (Universitas Islam Negeri Raden Intan Lampung, 2022)
The Property Research Institute, Savills Indonesia projects that the supply of apartments will increase by 129,000 units by 2022 , therefore it is certain agents property and marketing will continue to grow but besides that they only think about profit without wanting to deepen their understanding of whether what they are doing is right or not. The purpose of this research is to know the practice profit sharing in marketing as well as the view of sharia economic law on practice profit sharing in marketing at CV Bonzela Property Apartement Grand Kamala Lagoon, Bekasi. This research uses a field study type approach (field research). The sources of data used are primary and secondary data, statements of sources and journals related to the thesis. Data collection techniques carry out by observation, Interview, and documentation. Data processing methods are carried out by editing data, systematizing data, and verification. The data analysis method used is a qualitative analysis approach in the method of inductive thinking. Based on the research results, it would be stated that the practice of profit sharing in marketing on CV Bonzela Property Apartment Grand Kamala Lagoon there is a fraud committed by marketing to the company by doing secret selling, which is only profitable marketing and harm CV Bonzela Property. as for the practice of profit sharing in marketing at CV Bonzela Property Grand Kamala Lagoon Apartment according to Islamic law is something that is prohibited in Islam, because there are many frauds committed by marketing against the company and it is unlawful or prohibited in Islam. Keywords: Apartments, Marketing, Profit Sharing